Biosensors (Global Journals of Research in Engineering, 2016)
In this paper aims to review how biosensors are made, where they can be used, their advanced and their detection methods. The biosensors are studied and fabricated to detect samples and measure demand values by using online websites that based on grounded theory. The paper reviewing some factors that help us to understand biosensor importance in our daily lives in most fields. Studies and researches are limited to real studies which has been collected from the result of experiment in various laboratories the suggested model is particularly useful for medical detecting to better illustrating and understanding the illness samples by display output of high resolution. In addition, they can be used in water treatment and food testing the paper shows design of biosensors, their application and types. Also; it highlights resolutions and sensitive the value that is detected by biosensors. Moreover, it presents simplicity of using biosensors So, it encourages the researches and inventors to focus on this challenge.
Keywords: biosensors; biomedical; hospital#x2019; s devices; biotechnology; biomedical engineering